Precision Measurement of the Boron to Carbon Flux Ratio in Cosmic Rays from 1.9 GV to 2.6 TV with the Alpha Magnetic Spectrometer on the International Space Station - AMS Collaboration (Physical Review Letters, 2016)
Knowledge of the rigidity dependence of the boron to carbon flux ratio (B/C) is important in understanding the propagation of cosmic rays. The precise measurement of the B/C ratio from 1.9 GV to 2.6 TV, based on 2.3 million boron and 8.3 million carbon nuclei collected by AMS during the first 5 years of operation, is presented. The detailed variation with rigidity of the B/C spectral index is reported for the first time. The B/C ratio does not show any significant structures in contrast to many cosmic ray models that require such structures at high rigidities. Remarkably, above 65 GV, the B/C ratio is well described by a single power law 𝑅Δ with index Δ=−0.333±0.014⁢(fit)±0.005⁢(syst), in good agreement with the Kolmogorov theory of turbulence which predicts Δ=−1/3 asymptotically.
Keywords: dept.phy

Antiproton Flux, Antiproton-to-Proton Flux Ratio, and Properties of Elementary Particle Fluxes in Primary Cosmic Rays Measured with the Alpha Magnetic Spectrometer on the International Space Station - AMS Collaboration (Physical Review Letters, 2016)
A precision measurement by AMS of the antiproton flux and the antiproton-to-proton flux ratio in primary cosmic rays in the absolute rigidity range from 1 to 450 GV is presented based on 3.49×1⁢05 antiproton events and 2.42×1⁢09 proton events. The fluxes and flux ratios of charged elementary particles in cosmic rays are also presented. In the absolute rigidity range ∼60 to ∼500 GV, the antiproton ¯𝑝, proton 𝑝, and positron 𝑒+ fluxes are found to have nearly identical rigidity dependence and the electron 𝑒− flux exhibits a different rigidity dependence. Below 60 GV, the (¯𝑝/𝑝), (¯𝑝/𝑒+), and (𝑝/𝑒+) flux ratios each reaches a maximum. From ∼60 to ∼500 GV, the (¯𝑝/𝑝), (¯𝑝/𝑒+), and (𝑝/𝑒+) flux ratios show no rigidity dependence. These are new observations of the properties of elementary particles in the cosmos.
Keywords: dept.phy

Precision Measurement of the Helium Flux in Primary Cosmic Rays of Rigidities 1.9 GV to 3 TV with the Alpha Magnetic Spectrometer on the International Space Station - AMS Collaboration (Physical Review Letters, 2015)
Knowledge of the precise rigidity dependence of the helium flux is important in understanding the origin, acceleration, and propagation of cosmic rays. A precise measurement of the helium flux in primary cosmic rays with rigidity (momentum/charge) from 1.9 GV to 3 TV based on 50 million events is presented and compared to the proton flux. The detailed variation with rigidity of the helium flux spectral index is presented for the first time. The spectral index progressively hardens at rigidities larger than 100 GV. The rigidity dependence of the helium flux spectral index is similar to that of the proton spectral index though the magnitudes are different. Remarkably, the spectral index of the proton to helium flux ratio increases with rigidity up to 45 GV and then becomes constant; the flux ratio above 45 GV is well described by a single power law.
Keywords: dept.phy

Precision Measurement of the Proton Flux in Primary Cosmic Rays from Rigidity 1 GV to 1.8 TV with the Alpha Magnetic Spectrometer on the International Space Station - AMS Collaboration; Finch, Evan (Physical Review Letters, 2015)
A precise measurement of the proton flux in primary cosmic rays with rigidity (momentum/charge) from 1 GV to 1.8 TV is presented based on 300 million events. Knowledge of the rigidity dependence of the proton flux is important in understanding the origin, acceleration, and propagation of cosmic rays. We present the detailed variation with rigidity of the flux spectral index for the first time. The spectral index progressively hardens at high rigidities.
Keywords: dept.phy